Missionaries and the colonial state - Whitehouse, David (Journalist), author.
1 online resource.
Keywords: "Catholic and Protestant missionaries followed their own, competing agendas rather than those of the colonial state. This volume unravels these agendas and challenges received wisdom on the histories of Rwanda and Burundi, as well as the colonial relationship between state and mission. Missionaries and the Colonial State is a resource for historians of Christianity, Belgian Africa specialists, and scholars of colonialism"--